Neoadjuvant target therapy followed by video-assisted thoracoscopic surgery lobectomy plus lymph node clearance for locally advanced lung cancer - Situ, Dongrong; Du, Yuansheng; Li, Yi; Chen, Jiyang; Yang, Hong (Journal of Thoracic Disease, 2019)
Although there is no robust evidence yet to support the application of EGFR-TKI as a neoadjuvant therapy for EGFR-mutant non-small cell lung cancer (NSCLC), successful case series have been reported previously in the literature. We demonstrate here one of our successful cases in which the patient proceeded to definitive surgery after his locally advanced NSCLC was significantly down-staged by EGFR-TKI.